Pamiętnik 1924-1939. 1981 (1981)
Dzieciństwo i wczesna młodość, życie rodzinne i środowisko miejskie przedwojennego Poznania.
Akc.: c 1986 710
Keywords: Wielkopolska; Poznań; m; miasto 20 w.; robotnicy 20 w. praca